Perancangan Aplikasi Perpustakaan Berbasis Website Pada SMA Negeri 1 Sajira Banten - Reza Sozzana; Priatno Priatno; Mohammad Aris (Sekolah Tinggi Ilmu Administrasi (STIA) Yappi Makassar, 2024)
Library is a supporting educational unit that must provide information and knowledge to learners because in their environment they can share information, so that learners have broad insight. The library system in SMA Negeri 1 Sajira is still using conventional or manual way in daily activities so that there are often mistakes in entering data, delay in the process of finding the necessary data and the accumulation of irregular archives. With the existing problem-based then created a software that can provide solutions to help librarians in the parent data - library data in SMA Negeri 1 Sajira and can accelerate student borrowing and repaying transactions.